Allergic TH2 Response Governed by B-Cell Lymphoma 6 Function in Naturally Occurring Memory Phenotype CD4+ T Cells - Ogasawara, Takashi; Kohashi, Yuko; Ikari, Jun; Taniguchi, Toshibumi; Tsuruoka, Nobuhide; Watanabe-Takano, Haruko; Fujimura, Lisa; Sakamoto, Akemi; Hatano, Masahiko; Hirata, Hirokuni; Fukushima, Yasutsugu; Fukuda, Takeshi; et al. (Frontiers in Immunology, 2018)
Transcriptional repressor B-cell lymphoma 6 (Bcl6) appears to regulate TH2 immune responses in allergies, but its precise role is unclear. We previously reported that Bcl6 suppressed IL-4 production in naïve CD4+ T cell-derived memory TH2 cells. To investigate Bcl6 function in allergic responses in naturally occurring memory phenotype CD4+ T (MPT) cells and their derived TH2 (MPTH2) cells, Bcl6-manipulated mice, highly conserved intron enhancer (hcIE)-deficient mice, and reporter mice for conserved noncoding sequence 2 (CNS2) 3′ distal enhancer region were used to elucidate Bcl6 function in MPT cells. The molecular mechanisms of Bcl6-mediated TH2 cytokine gene regulation were elucidated using cellular and molecular approaches. Bcl6 function in MPT cells was determined using adoptive transfer to naïve mice, which were assessed for allergic airway inflammation. Bcl6 suppressed IL-4 production in MPT and MPTH2 cells by suppressing CNS2 enhancer activity. Bcl6 downregulated Il4 expression in MPTH2 cells, but not MPT cells, by suppressing hcIE activity. The inhibitory functions of Bcl6 in MPT and MPTH2 cells attenuated allergic responses. Bcl6 is a critical regulator of IL-4 production by MPT and MPTH2 cells in TH2 immune responses related to the pathogenesis of allergies.